Islamic Education in the Perspective of Islam Nusantara - Sirait, Sangkot (Jurnal Pendidikan Islam, 2016)
Indonesia has many islands, ethnic and cultures. Each culture has a different character, and it looks on the pattern of life measures to any area where they live. In the life of Indonesian society, all most social and religious activities can not be separated from the rituals and culture, in the ceremonies of birth, marriage and death. Religion and culture converge in life. Sometimes it is difficult to distinguish whether it is religious rituals or cultural aspects. This is exactly the essence of Islam Nuantara. The number of variants in cultural influence on people’s lives, including educational institutions. Islamic education as an institution and the system should be involved in responding to this situation. Moreover, Islamic education it self is in a community that has a lot of culture. Islamic education should not be viewed Islam Nusantara as an emerging concept, developed or even disappear, but Islamic education makes the discourse can help in the formulation of educational system. Many things should be set within the context of Islam Nusantara, for example curriculum, reference, methodology, teacher qualifications and infrastructure. All elements refer to the appreciation of culture in religious education.